The southern African inland fish tracking programme (FISHTRAC): An evaluation of the approach for monitoring ecological consequences of multiple water resource stressors, remotely and in real-time. (April 2020) - Burnett, Matthew J.; O'Brien, Gordon C.; Jacobs, Francois J.; Botha, Francois; Jewitt, Graham; Downs, Colleen T.
Highlights: We evaluated the southern African inland fish tracking (FISHTRAC) programme. FISHTRAC's functionality, real-time and remote application were highlighted. FISHTRAC was implemented in five economically important freshwater ecosystems. A four-phase guideline to successfully implement radio telemetry is provided. FISHTRAC contributes to understanding water resources with continued stressors. Abstract: Fishes are indicators of aquatic ecosystem wellbeing globally and used when understanding impacts from water resources. The behavioural ecology of fishes as a Line of Evidence (LoE) is between 10 and 100 times more responsive to changes in environmental variables, compared with traditional LoEs including standard mortality bioassay LoEs. Fish telemetry methods are available to monitor fish behaviour and the response of tagged fish to altered water quality, flow and instream habitat variability exist globally. Developing regions have relatively poor use of fish telemetry as a methodology to gather behavioural information, compared with developed regions for various reasons. Fish telemetry methods can assist in answering water resource management questions faced in developing regions. For this purpose, we describe the development of the southern African inland fish tracking (FISHTRAC) programme and its use for collecting fish behaviour, and water quality and quantity data in real-time and remotely. We also detail eight case studies that contributed to FISHTRAC over the past decade. The FISHTRAC programme was initially based on internationally recognised radio telemetry methods that were then adapted for application in southern Africa. Developments within the FISHTRAC programme have seen radio telemetry methods expand beyond manual monitoring techniques to incorporate a real-time and remote monitoring feature. The case studies demonstrated the development of FISHTRAC's functionality; data management systems, real-time communications and data evaluations. This included its implementation in five economically important freshwater ecosystems across southern Africa and using eight large charismatic fish species. Following the description of the FISHTRAC programme, we provide a four-phase guideline to successfully implement radio telemetry methods to obtain behavioural information of fishes and contribute to the essential management and monitoring of fisheries and water resources within the southern Africa context, applicable globally with continued anthropogenic stressors.